A Spatial, Non‐parametric Analysis of the Determinants of Food Insecurity in Sub‐Saharan Africa. (12th June 2015) - Sassi, Maria
Abstract: This paper investigates the determinants of food insecurity at the macro‐level in cross‐sectional data for a sample of 40 countries in sub‐Saharan Africa and considers the most basic causes of undernourishment, including food availability, access to food and its utilization. The empirical analysis is based on a spatial, non‐parametric technique that allows global and local explanatory variables to be distinguished from one another. The results provide useful information for reconsidering food security policies and programmes that extend beyond the prevailing perspective of food availability and suggest possible directions for regional and sub‐regional approaches to the food crisis in sub‐Saharan Africa.